Clawback Provision of SOX, Financial Misstatements, and CEO Compensation Contracts - Natarajan, Ramachandran; Zheng, Kenneth (Journal of accounting, auditing & finance, 2019)
Section 304 of the Sarbanes-Oxley Act (hereafter, SOX), commonly known as the clawback provision, entitles the Securities and Exchange Commission (SEC) to sue the CEO and CFO in an attempt to recover their incentive compensation based on misstated financial reports. Although a stream of literature investigates the effects of voluntary firm-initiated clawback provisions, this study explores the effects of the mandatory SOX clawback provision on the likelihood of financial misstatements and CEO compensation. We find a significant decrease in the association between CEO in-the-money option value and the likelihood of a financial misstatement surrounding SOX, suggesting the SOX clawback provision has been effective in reducing financial misstatements arising from CEO in-the-money stock options. To examine the effects of the SOX clawback provision on CEO compensation, we identify a set of misstatement firms with a high restatement likelihood where the CEOs are most likely concerned with the impact of the SOX clawback provision on their compensation. We find that compared with control firms, these misstatement firms with a high restatement likelihood where the CEO is the chair of the board exhibit an increase in CEO salaries between the pre- and post-SOX periods, suggesting that in the post-SOX period, powerful CEOs are able to receive higher salaries which are not subject to the SOX clawback provision.